Analysis of Employment and Economic Patriotism: A Case of Nepal (Patan Pragya, 2021)
Deficiency in demand is the host of almost all economic problems in the modern world.Economic growth and rate of employment has positive relations, but productivity of workers inversely affects the employment growth. Employment challenge in a developing country like Nepal may manifest in several forms. Firstly, there is a quantitative dimension in employment that employment growth may fall short of labour force growth giving rise to open unemployment. Secondly, low productivity earnings associated with a sizeable segment of the employed population. Eemployment patriotism is the judicial blend of employment and economic patriotism. Every government action is needed to be guided by employment generation motives. In addition to the increased pressure due to an unprecedented volume of COVID-19 induced returnees, the economic downturn due to the pandemic may also reduce the global demand for migrant workers. In such an alarming case, Nepal needs to prepare for employment patriotism policy.